ANALISIS KOMPARASI BATAS USIA NIKAH DI INDONESIA DAN MALAYSIA - Adi Gunawan Harahap; Hermita Panda Hasibuan; Muhammad Ichsan (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2025)
The age of marriage in Indonesia according to the 1974 marriage law is 16 years for men and 16 years for women. Then the regulation was revised in law number 16 of 2019 to make the minimum age for marriage for men and women to be 19 years. Malaysia also has minimum marriage regulations in Islamic family law that states that men must be at least 18 years old and women must be at least 16 years old. This research will discuss the comparative comparison of marriage age policy rules and the philosophy of the legal rules that apply between Indonesia and Malaysia. This research uses a descriptive qualitative approach. The result of this article is that the policies made by the two countries have the same goal, one of which is preventing early marriage. And also the marriage age regulations are more effective than the regulations that apply in Malaysia, due to the very strong influence of cultural customs, they are not applied to all Malaysian people, the adult category in Malaysia is 18 years but usually the minimum marriage for women is still 16 years.